Kajian Empiris dan Etnofarmakologi Tumbuhan Hutan Berkhasiat Obat asal Desa Tumbang Rungan Kelurahan Pahandut Kota Palangkaraya Kalimantan Tengah - Nurul Qamariah; Rezqi Handayani; Susi Novaryatiin (Anterior Jurnal, 2018)
Tumbang Rungan Village is one of the villages located in Pahandut District, Palangka Raya City, Central Kalimantan. This village is one of the locations that have great potential for medicinal herbs (THBO). Many traditional medicines are marketed in the Central Kalimantan region made from THBO from the village of Tumbang Rungan. THBO from Tumbang Rungan Village is believed by the community to be able to treat various diseases including treating tonsillitis, coughing, asthma explosions, stamina enhancer in men, antidiabetic, diuretic, and healing wounds. But this is still empirical, and there is no scientific data. Therefore, this research was conducted to inventory THBO from Tumbang Rungan Village and do a literature study to look for experimental data on both active compounds and pharmacological effects compared to practical ones. The results of the survey obtained eleven THBO from Tumbang Rungan Village which is efficient as traditional medicines. Nine plants including scientific data have been collected regarding active compounds and their pharmacological effects. The results of this study can later become a reference for further research to develop the local potential of Central Kalimantan in traditional medicine.